Level of customer satisfaction toward PROTON cars/ Nur Syazana Mohd Nizar - Mohd Nizar, Nur Syazana (Faculty of Business and Management, 2010)
As requirement by subject Industrial Training Report (OPM 662), I have completed this research on “level of Customer Satisfaction toward Proton Sendirian Berhad cars”. In this research four independent variables that affect customer satisfaction level have been identified which are cost, product design, quality and service. Research has been doing on customer of Proton at Tanjung Malim. I have taken 100 people to be my respondents in Tanjung Malim that means I used 100 samples on this research. Objectives of the study are to investigate the problems faces by customer at Proton, to identify the level of customer satisfaction toward this organization, to examine the most elements that influence customer satisfaction, and to give some recommendations to Proton in order for improvement in future. Finding on this research, we will know the level of customer satisfaction of Proton and also measure the relationship between customer satisfaction with cost, product design, quality and service.